Sin, shame, and the subject - Jorgenson, Allen G. (Dialog : a journal of theology, 2023)
In this chapter I revisit construals of sin and shame, beginning with a moment of auto‐investigation. I then set this data in conversation with historical, theological, and philosophical configurations of shame to reconceive sin and shame. I describe sin as curvatus ex carne (turning from the flesh) to signal sin as a refusal of both our embodied existence and a commodification of the land on which it lives. I then use a carnal hermeneutic to argue for a positive understanding of discerning shame as a resource for an ethical life that contrasts with shame of disgrace.